Physico-Chemical Parameters of Textile Dyeing Effluent and Its Impacts with Case study - Gomathi Elango; Rathika G.; Santhini Elango (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
This study focused on the quality of textile dyeing effluent by analyze the physico-chemical parameters such as colour, pH, total hardness, biological oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), total suspended solids (TSS), turbidity, chlorides, sulphides, silica, calcium, iron, oil and grease of the effluent. The results of the analysis were correlated with the water quality standards of BIS (Bureau of Indian Standard). It was confirmed that all the parameters studied above guideline permissible limits excluding calcium, sulphide and iron. Also this paper included the case study of textile dyeing industry, Tirupur district, Tamilnadu, India and its impacts with suggestions and policies in terms to reduce pollution load on environment.